It's Contagious! Examining Gamified Refutation Texts, Emotions, and Knowledge Retention in a Real-World Public Health Education Campaign. Issue 5 (3rd July 2022) - Trevors, Greg; Ladhani, Farhaan
ABSTRACT: The current study investigated the relations between gamified refutations of COVID-19 misconceptions and individuals' emotional reactions and knowledge retention within a large-scale public health education campaign. Refutations have a substantial body of evidence supporting their use to correct misconceptions, yet reduced efficacy has been observed for some topics that generate negative emotional responses. We tested whether gamification could mitigate these limits given that it capitalizes on positive affective engagement. From May to December 2020, approximately 200, 000 individuals were recruited from social media in Canada to engage with a nongame interactive survey as a control or a fully gamified platform focused on correcting COVID-19 misconceptions. Gamification was associated with a greater number of happiness and anxiety responses and fewer responses of anger and skepticism in reaction to having misconceptions corrected by refutations. Further, participants who engaged with gamified refutations retained correct information after a brief period. Finally, happiness and anxiety were positively associated with and anger and skepticism were negatively associated with retention of refutation information and support for related public health policies. Implications for scaling up and reinforcing the benefits of refutations for public engagement with science are discussed.